2017
DOI: 10.1016/j.physbeh.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming neonatal sickness: Sex-specific effects of sickness on physiology and social behavior

Abstract: Early-life environmental stressors, including sickness, have the potential to disrupt development in ways that could severely impact fitness. Despite what is known about the effects of sickness on reproduction, the precise physiological mechanisms have not yet been determined. The goal of this study was to investigate the effects of a neonatal immune challenge on adult reproductive physiology and opposite-sex social behavior. Male and female Siberian hamster (Phodopus sungorus) pups were administered lipopolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 64 publications
1
16
1
Order By: Relevance
“…Specifically, in order to test the hypothesis that early-life activation of the immune system has long-term consequences on how the gut microbiome and behavior respond to antibiotic treatment in adulthood, we mimicked an early-life infection by injecting pups with LPS and subsequently, exposing those same animals to antibiotic treatment in adulthood to target the microbiome directly. In our previous work, we have shown that early-life LPS did not influence same-sex social behavior in either sex, though we found that LPS-treated females exhibited more aggression with and investigation of male conspecifics in a reproductive context compared to saline controls (Sylvia et al, 2018; Sylvia and Demas, 2017). Here, we hypothesized that individuals treated with exogenous LPS in early life would exhibit more robust physiological and behavioral changes following adult antibiotic treatment.…”
Section: Introductioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Specifically, in order to test the hypothesis that early-life activation of the immune system has long-term consequences on how the gut microbiome and behavior respond to antibiotic treatment in adulthood, we mimicked an early-life infection by injecting pups with LPS and subsequently, exposing those same animals to antibiotic treatment in adulthood to target the microbiome directly. In our previous work, we have shown that early-life LPS did not influence same-sex social behavior in either sex, though we found that LPS-treated females exhibited more aggression with and investigation of male conspecifics in a reproductive context compared to saline controls (Sylvia et al, 2018; Sylvia and Demas, 2017). Here, we hypothesized that individuals treated with exogenous LPS in early life would exhibit more robust physiological and behavioral changes following adult antibiotic treatment.…”
Section: Introductioncontrasting
confidence: 56%
“…These molecules can then act on the brain to initiate the acute-phase response (APR), including fever, lethargy, decreased food intake, and enhanced pain response (Harvey and Boksa, 2012; Perry, 2004; Quan and Banks, 2007). Previous research in our lab has shown that early-life LPS influences investigation and aggression and affects reproductive physiology in females, but not in males (Sylvia and Demas, 2017).…”
Section: Introductionmentioning
confidence: 83%
“…LPS injection through peritonea induced the activation of microglia accompanied with sickness behavior, which suggested that the peripheral inflammation connected the brain response [53]. In the present study, at early stages after aggression, plasma GC increased.…”
Section: Researchsupporting
confidence: 61%
“…Corticosterone levels were also elevated in neonatal LPStreated females across developmental timepoints (Sominsky et al, 2012). LPS-treated female Siberian hamsters have abnormal estrous cycles and smaller ovaries relative to saline controls, while male testes mass is not affected (Sylvia & Demas, 2017).…”
Section: Discussionmentioning
confidence: 92%
“…For example, neonatal LPS decreases social interaction time in female rats tested during adolescence (Doenni et al, 2016;MacRae et al, 2015). In Siberian hamsters, PND3 LPS-treated females investigate an opposite-sex conspecific more and spend more time in attack bouts than saline-treated females (Sylvia & Demas, 2017). LPS administration at later developmental timepoints also influences female social behaviors.…”
Section: Discussionmentioning
confidence: 99%